Tingkat Pengetahuan dan Pelaksanaan Pap Smear Pada Ibu Pasangan Usia Subur di Dusun Kemasan Desa Karang Tengah Imogiri Bantul Tahun 2015 - Chusnul Khotimah; Dyah Noviawati Setya Arum; Munica Rita Hernayanti (Poltekkes Kemenkes Yogyakarta, 2017)
Cervical cancer is the second most common cancer in the world. In developing countries still ranks first as a cause of cancer deathsin women of reproductive age. Pap smear has proved very useful for early detection of cervical cancer since pre-cancerous stage,but many women are reluctant to undergo a pap smear because of ignorance, shame, fear, and cost factors. While the Pap smearcoverage lowest in Imogiri health center II is 0%. The type of research is a descriptive study with cross-sectional approach. Todescribe the level of knowledge and overview of the implementation of Pap smears in women in fertile age couple in the KemasanHamlet Karang Tengah Village Imogiri Bantul. The entire population of mothers in fertile age couple who attended of the PKK andwilling to become respondents in the Kemasan Hamlet Karang Tengah Village Imogiri Bantul. The results of research that themajority of respondents aged> 35 years (51.1%), basic education (50%), does not work (53.44%), obtain resources through onesource (63.3%). The level of knowledge about Pap smears in women PUS (Pasangan Usia Subur) in the Kemasan Hamlet KarangTengah Village Imogiri Bantul 2015 is in the category enough that 72.7% and most did not carry out pap smear that is, 86.4%. Theconclusion that the level of knowledge about the EFA mother pap smear EFA in the Kemasan Hamlet Karang Tengah Village ImogiriBantul 2015 enough and did not carry out pap smear.